Exploring The Role of Frugal Living and Digital Financial Inclusion to Saving’s Intention Within Indonesia’s Gen Z - Alim, Abdul Malik; Margareta, Ananda Maya; Yuanna, Destin; Maharani, Anita (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyse the influence of frugal living lifestyle and digital financial inclusion on saving intention among Generation Z in Indonesia. Conceptually, frugal living, which is increasingly popular among Generation Z, refers to a frugal lifestyle that includes wise financial management to achieve long-term goals. Meanwhile, digital financial inclusion reflects easy access to technology-based financial services that can facilitate the saving process. This study uses a quantitative approach with a questionnaire distributed to Generation Z in Indonesia, resulted in 70 respondents. The results of the regression analysis show that frugal living and digital financial inclusion have a positive and significant influence on saving intention, where frugal living has a stronger influence. In addition, it was found that these two factors complement each other in increasing saving intention, because digital access makes it easier to implement a frugal lifestyle. These findings provide implications for banks in Indonesia to develop marketing strategies that promote a frugal lifestyle and provide digital banking services that are responsive to the needs of Generation Z.